Blockchain-Enabled Compliance Architecture: A Decentralized Framework for Financial Cloud Infrastructure Governance - Venkata Surya Hanuma Sivakrishna Penugonda (Journal of Computational Analysis and Applications (JoCAAA), 2026)
Incorporating blockchain technology into financial cloud infrastructure changes the way regulatorycompliance is attained and transparent audit trails are preserved. Conventional compliance systemsdepend on central authorities and manual verification procedures, which sometimes lack real-time visibility and expose weaknesses in trust systems